Anterolateral Capsule Injury Did Not Aggravate Rotational Laxity of the Anterior Cruciate Ligament Injured Knees Measured by Quantitative Pivot-shift Evaluation. Issue 7 (21st July 2017) - Miyaji, Nobuaki; Hoshino, Yuichi; Tanaka, Toshikazu; Nishida, Kyohei; Nishizawa, Yuichiro; Araki, Daisuke; Kanzaki, Noriyuki; Matsushita, Takehiko; Kuroda, Ryosuke
Objectives: The anterolateral capsule (ALC) injury concomitant with the anterior cruciate ligament (ACL) injured knees has been recently focused with potential effect on the knee rotational laxity. Although some basic in-vitro studies explored the effect of the additional ALC injury, most of such studies utilized their original rotational stress test rather than the clinically-used pivot-shift test. The knee rotational instability should be examined by the clinical pivot-shift test. Some quantitative measurement devices for the pivot-shift test have been clinically available lately. The purpose of this study were to evaluate the pivot-shift test using a quantitative measurement in clinical cases and to compare them between ACL injured knees with and without the ALC injury determined by magnetic resonance imaging (MRI). Methods: Eighty-five unilateral ACL injury patients (40 male and 45 female, age 25.3±11.7 y.o.) who were scheduled to have primary ACL reconstruction were included. Just prior to the ACL reconstruction, the pivot-shift test was performed under anesthesia while making the quantitative evaluation using electromagnetic measurement system (Fig.1). The tibial acceleration (m/sec 2 ) during the pivot-shift was calculated, and the four levels of clinical grading was also determined according to the IKDC (none, glide, clunk, and gross). The concomitant ALC injury in the ACL injured knees was diagnosed on the MRI and divided into two groups ALC injured group (ALC+) and ALC intact group (ALC-). The differences of clinical grading and quantitative measurements were tested between ALC+ and ALC- groups. P-value of <0.05 was considered as statistically significant. Results: Forty-two patients had concomitant ALC injury. 21 knees of ALC+ group were graded as glide in clinical grading, 18 knees as clunk, and 3 knees as gross in ALC+ group, meanwhile 22 knees were assessed as glide, 17 knees as clunk, and 3 knees as gross in ALC- group. There was no difference in clinical grading between ALC+ and ALC- groups (p=0.97). The tibial acceleration measurement during the pivot-shift test demonstrated no significant difference between ALC+ group (1.4±1.2 m/sec 2 ) and ALC- group (1.6±1.3 m/sec 2 ) (p=0.21). Conclusion: This study demonstrated that the ALC injury accompanied with the ACL injury did not have significant effect on the rotational laxity based on either clinical grading or quantitative evaluation. There was a limitation of this study that statistical power was not so strong around 0.6, but, interestingly, the rotational laxity measurements was slightly larger in the ALC intact group. The ALC injury has been advocated as a major factor to aggravate the knee rotational laxity. In this study, however, the impact of the ALC injury on the rotational laxity was not confirmed. Therefore, we should pay more attention to other common and identifiable injures such as meniscus and cartilage tear.